ANALYSIS AND STUDY ON 47 CASES OF ADVERSE REACTIONS OF CHINESE MEDICINE INJECTION - Zhang, Xiaoyu; Sang, Dechun; Zhang, Zhiqiang; Kong, Shuangyan (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Along with efficacy, Chinese medicine is increasingly being known to people, Chinese medicine and its preparations are increasingly widespread in clinical use. People generally believe that Chinese medicine has few side effects and is safe, especially Chinese medicine injections. Due to the direct injection in blood, rapid onset and good efficacy, they are welcomed by people. However, with increased use, adverse reactions are increasing, even causing serious consequences. The objective is to learn about the characteristics and laws of the adverse effects of Chinese medicine injections, provide references for the clinical safe drug use, and reduce the incidence of adverse reactions. Materials and Methods: The method was established to analyze the data of 47 cases of adverse reactions caused by Chinese medicine injections in our hospital from the year, 2009 to 2010.Results: The organs / systems involved in the 47 cases of adverse reactions are primarily skin and its accessories and secondly systemic damage, involving a total of eight varieties of drugs. Conclusion: The adverse reactions of Chinese medicine injections are mostly in Chinese patent drugs, which should be paid attention to, to find out the problems and laws, use the drugs rationally, and reduce the incidence of the adverse reactions.